Keterlibatan Kerja pada Anggota Kepolisian: Tinjauan Sistematis terhadap Faktor-faktor yang Meningkatkan Keterlibatan Kerja - Agustina Inesia; Bonita Sandika; Eka Putri; Phyu Sin Yadanar Thein (Publikasi Indonesia, 2024)
Work involvement is an important phenomenon in the context of organizations, especially in demanding environments such as the police. The purpose of this study is to analyze and explain the factors that can increase work engagement in police membership. This study is a systematic literature review with samples in the form of secondary data from journals searched through Google Scholar, Publish or Perish, Academia.edu, and PubMed Central. The main keywords and focus of this study are